Development Of E-Research Information System To Support Research Management (Case Study of Wastukancana University) - Bayu Prasetio; Irsan Jaelani (Journal of Computer Networks, Architecture and High Performance Computing, 2022)
E-research management is an implementation mechanism of information and communication technologies on the research management so that the research runs effectively and efficiently. E-research STT Wastukancana is an information system for submission of a thesis title and undergraduate internship but there are still many incomplete features, so it needs system development so the system can run well. Therefore author does the development system of e-research STT Wastukancana Web-Based so that admin, students, and lecturers can carry out business processes well on online system mode. The result of this research is an information system that can help out and ease users in doing business processes and information around e-research STT Wastukancana